Determination of radon concentration in bottled drinking water of Dhaka City - Pervin, Shikha; Yeasmin, Selina; Khandaker, Mayeen Uddin *; Begum, Afia (Taylor and Francis Group, 2024)
Among all natural radiation sources, exposure to radon (222Rn) is considered as the most hazardous to human health. Recognizing the significance of water in preserving a healthy life style, assessing the 222Rn activity in drinking water is crucial. The 222Rn activity concentration was measured in 20 different branded bottled drinking waters purchased from Dhaka city using both alpha and gamma-ray spectrometry systems. Activity concentrations of 222Rn in bottled water obtained via RAD7 detector varied from 0.1 ± 0.02 Bq/L to 0.42 ± 0.01 Bq/L with an average value of 0.26 ± 0.02, while the value varied from 0.12 ± 0.01 Bq/L to 0.52 ± 0.31 Bq/L with an average value of 0.29 ± 0.09 by HPGe detector. The obtained results show lower concentrations when compared with other studies around the world as well as the US-EPA reference level of 11.1 Bq l−1 or 300 pCi l−1. The total annual effective dose calculated for different age groups and internal organ doses were found below the action level recommended by WHO (0.1 mSv y−1) and ICRP (3–10 mSv y−1), due to 222Rn, 3H and 40K in drinking water. Based on the obtained radon concentration and concomitant dose values, this study suggested negligible health hazards due to the consumption of bottled drinking water in Bangladesh. The results of this study could serve as a reference data for future studies in the area and beyond.